Individualized education focusing on self‐management improved the knowledge and self‐management behaviour of elderly people with atrial fibrillation: A randomized controlled trial. Issue 4 (4th March 2021) - Oh, Yun Hee; Hwang, Seon Young
Abstract: Aim: This study examined the effect of an individualized educational intervention on the knowledge, attitudes and self‐management ability after 12 weeks for outpatients with atrial fibrillation. Methods: A randomized control‐group pretest‐post‐test experimental design was used. Elderly outpatients with atrial fibrillation aged over 65 years were recruited from a university hospital in Korea. The experimental group received a 50‐min individualized education on self‐management, one telephone counselling after 8 weeks and maintenance of a self‐management diary for 12 weeks. Data were collected from November 2017 to April 2018 and analysed using SPSS 22.0 for descriptive statistics and hypothesis testing. Results: The participants' mean age was 71.9 (4.6) years. Compared to the control group ( n = 29), the experimental group ( n = 31) showed a significantly greater improvement in knowledge regarding atrial fibrillation and stroke prevention ( t = −2.27, p = .027) and self‐management behaviours ( t = −8.02, p < .001). There were no significant group differences in attitudes towards atrial fibrillation. Conclusion: The findings suggest that education for elderly people with atrial fibrillation should be individualized, focusing on self‐management in daily life to prevent cardiovascular complications. Future research is needed to confirm the long‐term effects of such education programmes. SUMMARY STATEMENT: What is already known about this topic? Older adults with AF tend to lack the knowledge and have inadequate self‐management skills regarding their illness. Their awareness of AF should be raised, especially regarding cardiovascular complications, such as stroke and heart failure, and prevention of complications. Patients with AF, mostly older people and those with comorbid conditions, need to be educated on the different approaches apart from the usual education to prevent developing strokes. What this paper adds? Individualized education focused on self‐management to prevent cardiovascular complications was more effective in increasing the knowledge and self‐management behaviour among Korean older adults with AF compared with those patients receiving routine medical education. Education for patients with AF should be tailored to meet the needs of older adults and those with comorbidities and focus on self‐management to prevent cardiovascular complications in daily life. The implications of this paper: Individualized education and telephone counselling can help improve knowledge of complications and self‐management among elderly people with AF. Health care professionals need to provide periodical counselling and education to elderly people with AF to enhance their self‐management behaviour in daily life to prevent cardiovascular complications.